Case reportDermoscopy on nevus comedonicus: a case report and review of the literature - Kamińska-Winciorek, Grażyna; Śpiewak, Radosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Nevus comedonicus (NC) is a very rare, benign hamartoma characterised by the occurrence of dilated, comedo-like openings, typically on the face, neck, upper arms, chest or abdomen. In uncertain cases, histopathological examination confirms the diagnosis. The authors suggest dermoscopy as a rapid and useful method of initial diagnosis of nevus comedonicus based upon its distinctive dermoscopic features. The dermoscopy reveals numerous light and dark-brown, circular or barrel-shaped, homogenous areas with prominent keratin plugs.